Numerical and Experimental Analysis of Thermal–Hydraulic Behavior in Heat Pipe Systems (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Heat pipes are highly efficient passive thermal management devices widely used in electronics cooling, energy systems, and aerospace applications due to their excellent heat transfer capability. This paper presents a comprehensive numerical and experimental investigation of the thermal–hydraulic behavior of a heat pipe system under varying heat input and operating conditions. A detailed numerical model is developed to simulate heat transfer, fluid flow, phase change, and pressure distribution within the evaporator, adiabatic, and condenser sections. The numerical results are validated through controlled experimental testing, focusing on temperature distribution, thermal resistance, heat transfer coefficient, and working fluid dynamics. The comparative analysis demonstrates good agreement between numerical predictions and experimental observations, confirming the accuracy of the proposed model. The results reveal the influence of heat input, working fluid behavior, and wick structure on overall thermal performance and hydraulic stability. The findings provide valuable insights for optimizing heat pipe design and enhancing their reliability and efficiency in advanced thermal management applications.